The effect of extensive and intensive production systems on the meat quality and carcass characteristics of Dohne merino lambs - Hanekom, Yvette (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MSc Food Sc (Food Science))--University of Stellenbosch, 2010.